Human Capital and Optimal Redistribution - Winfried Koeniger; Julien Prat (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We characterize optimal redistribution in a dynastic economy with observable human capital and hidden ability. We compute the optimal allocation and show how it can be implemented with student loans or means-tested grants. The numerical results reveal that human capital investment should decline in parental income because parents with high income bequeath more and this lowers the labor supply of their children through a wealth effect.
Keywords: E24; H21; I22; J24; 330